Microwave-induced magnetooscillations and absolute negative conductivity in the multisubband twodimensional electron system on liquid helium - Monarkha, Yu.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
It is shown that a nonequilibrium filling of an upper surface subband induced by the microwave resonance can be the origin of the absolute negative conductivity and zero-resistance states for the two-dimensional electron system on liquid helium under magnetic field applied normally. Contrary to the similar effect reported for semiconductor systems, an oscillating sign-changing correction to the dc-magnetoconductivity appears due toquasi-elastic inter-subband scattering which does not involve photons. The analysis given explains remarkablemagnetooscillations and zero-resistance states recently observed for electrons on liquid helium.